Self-assessed Oral Health Awareness and Attitude of the First and Final Year Undergraduate Medical and Dental Students in India - Jacob, Sanjay; Saify, Mansoor; Jain, Divya Kumar; Paiwal, Kapil (Journal of Orofacial Research, 2014)
Aims and Objective: To compare the attitude and awareness of dental and medical students in the first and the final academic years and to trace the change in their attitude and awareness towards oral health; to also bring out differences/similarities in response to the questionnaire based on gender. Materials and methods: A modified version of HU-DBI questionnaire was used to conduct the survey in medical and dental colleges of India. A total of 279 students were recruited in the study. The data collected concerned the oral hygiene awareness and attitude, dental complaints and previous visits to dentists. Results: Significant differences were found for 9 of 17 items, reflecting an increased awareness and improved attitude toward oral health in the final year dental students as compared to the first year dental students. The dental students exhibited better awareness than the medical students irrespective of gender. Conclusion: Significant improvement was found in the awareness and attitude of the final year dental students as compared to the first year dental students. This change was marginal in the medical students.